THE NUTRACEUTICAL ROLE OF HOLY BASIL (TULSI) LEAVES IN PREVENTING ORAL AND CHRONIC DISEASES - I Gusti Ayu Ari Agung Buari; Dewa Made Wedagama; I Gusti Agung Ayu Hartini (International Journal of Applied Science and Sustainable Development (IJASSD), 2025)
The leading cause of global morbidity and mortality is chronic disease, which is related to lifestyle. Since the COVID-19 pandemic occurred, WHO has strongly appealed, especially for developing countries, for therapy to return to using natural ingredients. For example, through a focus on healthy lifestyle practices and regular consumption of adaptogenic herbs. Of all the herbs used, Holy Basil (Tulsi) is the most superior, and scientific research now confirms its beneficial effects. Tulsi leaves have been proven to be able to overcome physical, chemical, metabolic and psychological stress. This research aims to determine the nutraceuticals of Tulsi leaves in treating oral and chronic diseases.  This research uses the Systematic Literature Review method, with 6 steps, namely (1) formulating questions (based on theory); (2) Conduct searches (on Scopus, Google Scholar, EBSCO, ProQuest, and Science Direct), which published articles from 2015 to 2025; (3) Determine relevant research; (4) Determine articles that come from diverse backgrounds; (5) Data extraction from individual studies; (6) Synthesis of results using narrative methods. The results of this research are the nutraceutical synergy of Tulsi leaves was proven to be superior in protecting organs and tissues against chemical stress from industrial pollutants and heavy metals, as well as physical stress due to prolonged physical activity, ischemia, physical restraint, and exposure to excessive cold and noise. The nutraceutical synergy of Tulsi leaves has also been proven to combat metabolic stress through normalization of blood glucose, blood pressure and lipid levels (protecting the heart organ), and psychological stress through positive effects on memory and cognitive function as well as through anxiolytic, antidepressant and anticancer properties. The synergy of Tulsi's broad-spectrum antimicrobial activity is superior, including activity against various human pathogens, including pathogens that cause various oral chronic diseases (caries and periodontics). The conclusion of this research is the nutraceutical synergy of Tulsi leaves is very good in treating oral chronic diseases (oral cancer, caries and periodontics), and chronic diseases (cancer, diabetes, hypertension, cardiovascular disease and stroke), and is superior among other herbs.